2023
DOI: 10.1007/s11103-023-01345-5
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical water extraction of Equisetum arvense biomass withdraws cell wall fractions that trigger plant immune responses and disease resistance

Abstract: Plant cell walls are complex structures mainly made up of carbohydrate and phenolic polymers. In addition to their structural roles, cell walls function as external barriers against pathogens and are also reservoirs of glycan structures that can be perceived by plant receptors, activating Pattern-Triggered Immunity (PTI). Since these PTI-active glycans are usually released upon plant cell wall degradation, they are classified as Damage Associated Molecular Patterns (DAMPs). Identification of DAMPs imply their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Despite these advances, it was even proposed that the slow progress in the study of glucantriggered immunity was due to the insensitivity of the Arabidopsis ecotype Col-0 to glucans (Fesel and Zuccaro, 2016). However, numerous studies published over the last decade have shown that Arabidopsis is a good system to study glucan-triggered immunity (Souza et al, 2017;Claverie et al, 2018;Johnson et al, 2018;Mélida et al, 2018;Locci et al, 2019;Wanke et al, 2020;Rebaque et al, 2021Rebaque et al, , 2023Zarattini et al, 2021;Tseng et al, 2022;Martín-Dacal et al, 2023). The studies of two research groups confirmed the data published by Aziz et al, (2007) a decade earlier on the ability of β-1,4-glucans to induce PTI responses in plants (Souza et al, 2017;Johnson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advances, it was even proposed that the slow progress in the study of glucantriggered immunity was due to the insensitivity of the Arabidopsis ecotype Col-0 to glucans (Fesel and Zuccaro, 2016). However, numerous studies published over the last decade have shown that Arabidopsis is a good system to study glucan-triggered immunity (Souza et al, 2017;Claverie et al, 2018;Johnson et al, 2018;Mélida et al, 2018;Locci et al, 2019;Wanke et al, 2020;Rebaque et al, 2021Rebaque et al, , 2023Zarattini et al, 2021;Tseng et al, 2022;Martín-Dacal et al, 2023). The studies of two research groups confirmed the data published by Aziz et al, (2007) a decade earlier on the ability of β-1,4-glucans to induce PTI responses in plants (Souza et al, 2017;Johnson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the emergence of immune priming using glycans from various sources has demonstrated efficacy in enhancing protection across different pathosystems, showcasing the potential of glycanbased technologies in plant defence (Klarzynski et al, 2000;Aziz et al, 2007;Gravino et al, 2015;Claverie et al, 2018;Rebaque et al, 2023). This concept has spurred the development of crop protection technologies focused on enhancing the natural resistance mechanisms of the plants to combat plant pathogens, promoting sustainable agricultural practices and reducing environmental impact (Conrath et al, 2015).…”
Section: Introductionmentioning
confidence: 99%